Innovative apartment buildings : new directions in sustainable design - Friedman, Avi, 1952- (Stuttgart : Edition Axel Menges, 2017)
Current design of apartment buildings is facing challenges of philosophy and form. Past approaches no longer sustain new demands and require innovative thinking. The need for a new outlook is propelled by fundamental changes that touch upon environmental, economic, cultural and social aspects that led to the writing of this book. The depletion of non-renewable natural resources and climate change are a few of the environmental challenges that prompted designers to reconsider conceptual approaches in favour of ones that promote a better suitability between buildings and their environments.
Keywords: Apartment houses -- Designs and plans; Apartment houses -- Environmental engineering; Sustainable buildings -- Design and construction